Technique of calligraphy - Aнипинa A. К.; Шәріпқaзы Н. (Journal of Oriental Studies, 2018)
This article explores history of the Chinese language, styles of Chinese calligraphy. In Chinese, there are several styles, all of have some features. Different styles – changed written work in different regions of China. They are associated with the changes in writing means. Every student who studies Chinese must first know the history of the emergence of the Chinese language.